Monetary dialogue 2009-2014: Looking backward, looking forward - Ansgar Belke (Intereconomics, 2014)
In response to the financial crisis, the ECB has had to adopt new instruments to support the euro area economy and preserve the integrity of the single currency. This has challenged the current framework of the Monetary Dialogue exercise. This paper briefly assesses the implications of enhanced transparency and "forward guidance" for the effectiveness of the ECB's policies. It then checks whether the Monetary Dialogue works, and if and how the current Monetary Dialogue framework needs to change in order to fulfil its goal.
Keywords: 330; Geldpolitik; Internationale Wirtschaftspolitik; EU-Politik; Eurozone; EU-Staaten